Effects of Netarsudil-Family Rho Kinase Inhibitors on Human Trabecular Meshwork Cell Contractility and Actin Remodeling Using a Bioengineered ECM Hydrogel - Bagué, Tyler; Singh, Ayushi; Ghosh, Rajanya; Yoo, Hannah; Kelly, Curtis; deLong, Mitchell A.; Kopczynski, Casey C.; Herberg, Samuel (Frontiers in Ophthalmology, 2022)
Interactions between trabecular meshwork (TM) cells and their extracellular matrix (ECM) are critical for normal outflow function in the healthy eye. Multifactorial dysregulation of the TM is the principal cause of elevated intraocular pressure that is strongly associated with glaucomatous vision loss. Key characteristics of the diseased TM are pathologic contraction and actin stress fiber assembly, contributing to overall tissue stiffening. Among first-line glaucoma medications, the Rho-associated kinase inhibitor (ROCKi) netarsudil is known to directly target the stiffened TM to improve outflow function via tissue relaxation involving focal adhesion and actin stress fiber disassembly. Yet, no in vitro studies have explored the effect of netarsudil on human TM (HTM) cell contractility and actin remodeling in a 3D ECM environment. Here, we use our bioengineered HTM cell-encapsulated ECM hydrogel to investigate the efficacy of different netarsudil-family ROCKi compounds on reversing pathologic contraction and actin stress fibers. Netarsudil and all related experimental ROCKi compounds exhibited significant ROCK1/2 inhibitory and focal adhesion disruption activities. Furthermore, all ROCKi compounds displayed potent contraction-reversing effects on HTM hydrogels upon glaucomatous induction in a dose-dependent manner, relatively consistent with their biochemical/cellular inhibitory activities. At their tailored EC50 levels, netarsudil-family ROCKi compounds exhibited distinct effect signatures of reversing pathologic HTM hydrogel contraction and actin stress fibers, independent of the cell strain used. Netarsudil outperformed the experimental ROCKi compounds in support of its clinical status. In contrast, at uniform EC50-levels using netarsudil as reference, all ROCKi compounds performed similarly. Collectively, our data suggest that netarsudil exhibits high potency to rescue HTM cell pathobiology in a tissue-mimetic 3D ECM microenvironment, solidifying the utility of our bioengineered hydrogel model as a viable screening platform to further our understanding of TM pathophysiology in glaucoma.